PATTERNS OF URANIUM-ORE LOCALIZATION IN THE DONO-DNIPROVSKA POTENTIAL URANIUM-ORE METALLOGENIC PROVINCE IN ASSOCIATION WITH LITHOSPHERE'S DEEP STRUCTURE - Kalashnyk, G.; Кuzmin, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The objective of the study is to identify the main patterns of uranium-ore localization in the Dono-Dniprovska potential uranium-ore province in association with lithosphere's deep structure. The analysis of geophysical, geological, petrological, radiogeochemical information on the features of the formation, placement of uranium occurrences of the different genetic types in the Dnieper-Donets aulacogen in close connection with the features of the deep structure of the lithosphere, asthenosphere, fault tectonics was carried out. The features of the deep structure of the lithosphere and their physical parameters that affect the conditions of intensive uranium ore genesis in the formation of the main geological industrial types of uranium deposits in the research area were revealed. According to analysis of geological materials (uranium bearing, features of sedimentary-volcanogenic and, to a lesser extent, crystalline rocks occurrence, variety of breaking tectonics at various levels of the geological section, groundwater circulation conditions, etc.) the most perspective for discovering of new uranium deposits horizons and strata assigned to uranium-bearing geological formation in this region were identified. Based on a joint analysis of the geological conditions of localization of uranium deposits, ore occurrences and manifestations of uranium mineralization, geological uranium-bearing formations, their prevalence and depth occurrence in the Dnieper-Donets aulacogen, the four most perspective for this region industrial types of uranium deposits have been identified. The practical significance of this research is to increase the efficiency of metallogenic forecasts by expanding the deep factors and regional criteria for uranium ore genesis of various genetic types specified to the study area. This makes it possible to reasonably determine the prospects of the territories for the possibility of forming uranium industrial ore concentration with the allocation of areas of their most probable localization.
Keywords: uranium; lithosphere; uranium-bearing geological formation; geological-industrial type; deposit; Dono-Dniprovska potential uraniumore province